Improvement of Asthma Therapy by a Novel Formoterol Multidose Dry Powder Inhaler - Moeller, Manfred; Grimmbacher, Stefanie; Munzel, Ullrich (Arzneimittelforschung, 2008)
The objective of this post-marketing surveillance (PMS) was the evaluation of efficacy, tolerability, and acceptance of the advanced formoterol (CAS 73573-87-2) multidose dry powder inhaler (MDPI) Formatris® 6 µg/12 µg Novolizer® (FN) in asthmatic patients (n = 5219) in a real-life setting. A total of 2727 patients (52%) received concomitant anti-inflammatory treatment exclusively via a budesonide Novolizer8 (BN).Efficacy of the FN was assessed by measurement of peak expiratory flow (PEF) and forced expiratory volume in one second (FEV1) before and after 4 weeks of therapy. The severity of cough, wheezing, diurnal dyspnea, nocturnal dyspnea and dyspnea on physical effort were assessed on a four-point scale, and a severity sum score was calculated. The patients’ satisfaction with the multiple feedback mechanisms, handling and safety of the FN was also assessed. The physicians judged the patient compliance and any improved inhalation reassurance due to FN control mechanisms in comparison with other inhalation systems.FN use (n = 2727) was associated with improved lung function. After 4 weeks, PEF increased by 26% (from 270 L/min to 340 L/min) and the median FEV1 increased by 24% (from 2.1 L to 2.6 L). The median severity sum score decreased from 8.0 before therapy to 3.0 after therapy. Most patients assessed the control mechanisms and safety functions of the FN as ‘very good’ or ‘good’. 96% of patients were satisfied with the optical control mechanism, 92% with the acoustic mechanism, 70% with the taste feedback, 89% with the dose counter and 76% with the overdose prevention. The majority of patients (95%) confirmed that the multiple feedback mechanisms reassured correct drug intake, with 83% rating the FN as ‘much better’ or ‘better’ than previously used inhalers. The physicians confirmed that in contrast to previously used inhalers the FN ensured correct inhalation in 87% of all patients. The physicians were satisfied with the patients’ compliance in 95% of cases. Finally, the majority of patients (98%) were highly satisfied with the correct inhalation feedback mechanism. 94% of patients intended to continue FN therapy beyond the study.Overall, FN reduced the patients’ asthma symptoms and improved lung function, possibly due to improved compliance with therapy. The correct inhalation feedback mechanisms and safety functions of the device were assessed very positively by patients and were considered by the physicians to be important in improving inhalation reassurance and patient compliance.
Keywords: Antiasthmatics, inhalation device; Asthma, management; CAS 73573-87-2; Formatris®, inhaler technique; Formoterol, inhalation; Novolizer®, inhaler technique